Prosedur dan Alur Invoice Supplier CV. Karjum Jaya Mandiri - Andi Dwi Yanuar; Risma Fitriani (Jurnal Ilmiah Wahana Pendidikan, 2022)
Invoice is the evidence of product or service sale generally used by those selling product. The invoice preparation plays a very important part in supporting the office activity because the printed invoice can serve as evidence of product releasing, product delivery evidence, as the evidence of collection, as the evidence of archive when some time an inspection is conducted and as the evidence of product return. To get a good invoice preparation, a good procedure is required as well. With the good procedure, the invoice preparation process could be implemented well. Author aimed to describe and to explain the procedure invoice flow in CV. Karjum Jaya Mandiri. This observation was conducted using descriptive qualitative type of observation, the one describing or depicting the procedure of invoice preparation in the form of sentences and based on the facts. The data source derived from information, event or activity. Techniques of collecting data used were direct observation, interview.